THE CONCEPT OF EDUCATION AND SOCIAL CHARGE CHANGE, MODERNIZATION AND DEVELOPMENT - Yessa Maulida; Firman; Riska Ahmad (Yayasan Citra Dharma Cindekia, 2021)
The national education system states that education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character and skills needed for themselves, the nation and the world. country. Social change is all changes in social institutions in a society that affect the social system, including values, attitudes, and behavior patterns among groups in society. In education, socio-cultural changes can be made, namely the development of knowledge, adjustment of values and attitudes that support development and mastery of various skills in using advanced technology to accelerate the development process.